A lead-iodide based single crystal semiconductor: exploring multi-orientation photoconductive behaviour via intervening isopropyl viologen component between the inorganic [Pb2I6]2−n wires. Issue 15 (29th March 2018) - Wang, Yifang; Zhang, Jie; Huang, Jia; Zhang, Haoyu; Fu, Zhiyong
Abstract : A lead-iodide single crystal semiconductor with multi-orientation photoconductive property and broad spectrum absorption has been designed and constructed by crystal engineering technique. Abstract : A lead-iodide single crystal semiconductor with multi-orientation photoconductive properties and broad spectrum absorption has been designed and constructed by a crystal engineering technique. A strong charge transfer band was formed via organic–inorganic intermolecular interactions, darkening the color of the crystal. Electron catcher viologen cations surrounding the inorganic [Pb2 I6 ] 2− n chains extended the conductive orientation from along the a -axis in its perpendicular direction, presenting an interesting multi-channel conductive single crystalline system.